Gnoseological Interpretation of the Logical Deduction Theory - Skersytė, Jūratė (Problemos, 1969)
The paper raises the methodological question of the gnoseological role of the logical deduction theory. Both the functional relativity of the deduction theory setting the aim to determine inner consistency of the propositional structure in the system of necessary connections and the objective content of the deduction theory are disclosed. Gnoseological content of two interrelated functions of deductive reasoning -the logical definition and theory construction -is disclosed on the basis of analysis of the deductive structure of propositions taken from various spheres of cognition. Criticism of empiricist and conventionalist interpretation of the logical deduction theory is given. The author points to some methodological inconsistency in the traditional materialistic treatment of the specific character of deductive sciences, in particular, mathematics. This treatment is favoured by some Marxists.